2015
DOI: 10.5761/atcs.oa.14-00227
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Bypass Surgery in Patients with Pulmonary Hypertension: Assessment of Early and Long Term Results

Abstract: IntroductionPulmonary hypertension (PH) is one of the main causes of increased mortality and morbidity rates in open heart surgery. Left heart disease is probably the most frequent cause of PH. 1) Left-sided ventricular or valvular diseases may lead to an increase in left atrial pressure, and the passive backward transmission of this pressure may result in increased pulmonary arterial pressure (PAP). 2) Despite intensive postoperative medical treatment, an increase is observed in mortality and morbidity rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…When the limited number of studies investigating the effect of pulmonary artery pressures and PHT on surgical outcomes after cardiac surgery were reviewed, it was observed that the studies included some methodological differences, and the results of the studies were inconsistent with each other. In the literature, some of these limited studies investigating the effect of PHT on surgical outcomes were conducted in patients undergoing conventional on-pump CABG 5,10,11 , while others were conducted on patients undergoing valvular heart surgery 12,13 . In a study conducted on 177 patients undergoing conventional on-pump CABG by Çatav et al 10 , the patients were divided into three groups according to their SPAP values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the limited number of studies investigating the effect of pulmonary artery pressures and PHT on surgical outcomes after cardiac surgery were reviewed, it was observed that the studies included some methodological differences, and the results of the studies were inconsistent with each other. In the literature, some of these limited studies investigating the effect of PHT on surgical outcomes were conducted in patients undergoing conventional on-pump CABG 5,10,11 , while others were conducted on patients undergoing valvular heart surgery 12,13 . In a study conducted on 177 patients undergoing conventional on-pump CABG by Çatav et al 10 , the patients were divided into three groups according to their SPAP values.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that early-term mortality rates following on-pump CABG were statistically similar, and there was no significant difference between both groups with respect to perioperative early mortality, while the PHT group had a greater inotrope requirement, a longer mechanical ventilation time, and an increased length of ICU stay. Moreover, Akca et al 11 assessed the effect of preoperative PHT on not only early-term but also long-term results by screening a larger patient population. Among 2325 patients undergoing elective isolated conventional on-pump CABG, 287 patients with high preoperative SPAP ≥30 mmHg were evaluated, and of them, 69 patients with complete data who were on follow-up were included in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary HTN is a noted cause of perioperative morbidity and mortality as pertains to cardiac surgery. Bypass itself can worsen pHTN acutely due to the release of inflammatory mediators from pulmonary endothelium, exacerbating any previous predilection to hypoxia [6]. The TR also routinely encountered in such patients is often a result of RV dilation, secondary to pHTN, which in turn is a result of MV stenosis.…”
Section: Introductionmentioning
confidence: 99%